Karakteristik Habitat Sirih Hutan (Aristolochia tagala) Sebagai Pakan Larva Triodes helena di Kawasan Taman Nasional Gunung Rinjani Resort Timbanuh - Abdul Hamid; Endah Wahyuningsih; Nurul Chaerani (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
The larvae or caterpillars of the Troides helena butterfly have the main food in the form of forest betel (Aristolochia tagala). This plant is an important food source and habitat for the larvae. In addition to being food for butterfly larvae, Aristolochia tagala is also known in ethnobotany. This study aims to identify the characteristics of the habitat, host plants of Aristolochia tagala, and the influence of environmental factors on its existence. Data collection was carried out through an exploratory survey with a purposive sampling method, where the research plot was determined based on the presence of Aristolochia tagala vegetation. The number of plots was determined using the 0.5% IS method. Data analysis included analysis of vegetation, environmental factors, and simple linear regression. The results showed that the composition and vegetation structure found at the seedling level were dominated by coffee (Coffea canepora); H'=medium; E=low; D=high, level of singkrang stakes (Macaranga rhizoindes); H'=medium; E=low; D=high, level of puspa poles (Schima wallichii); H'=high; E=low; D=height and, at the bajur tree level (Pterospermum javanicum); H’=high; E=low; D=high. Habitat characteristics such as temperature, humidity, light intensity, pH, and altitude are in the optimal range. The host plant with the highest frequency was found in bajur stands (Pterospermum javanicum). The results of the regression test showed that humidity and altitude had a positive relationship, although with a very low coefficient of determination.